Lithium poisoning in the intensive care unit: predictive factors of severity and indications for extracorporeal toxin removal to improve outcome. (13th September 2016) - Vodovar, Dominique; El Balkhi, Souleiman; Curis, Emmanuel; Deye, Nicolas; Mégarbane, Bruno
Abstract: Context: Lithium is responsible for life-threatening poisoning, not consistently improved by extracorporeal toxin removal (ECTR). Objective: Our aim was to identify predictive factors on admission of poisoning severity and based on an evaluation of practice, report indications for ECTR susceptible to improve outcome Methods: We performed a retrospective cohort study including all lithium-poisoned patients admitted to the ICU in a university hospital. The usual clinical, biological and toxicological variables were collected. Poisoning severity was defined by seizures, catecholamine infusion, mechanical ventilation >48 h and/or fatality. Univariate followed by multiple logistic regression analyses were performed to identify prognosticators of poisoning severity and ECTR use. Results: From 1992 to 2013, 128 lithium-poisoned patients including acutely (10%), acute-on-chronically (63%) and chronically poisoned patients (27%) were included. The presumed ingested dose of lithium was 17.0 g [8.0–24.5] (median [25th–75th percentiles]). Serum lithium concentrations were 2.6 mmol/l [1.5–4.6], 2.8 mmol/l [1.8–4.5] and 2.8 mmol/l [2.1–3.0] on admission, peaking at 3.6 mmol/l [2.6; 6.2], 4.3 mmol/l [2.4; 6.2] and 2.8 mmol/l [2.1; 3.1] in the three groups, respectively. Severe poisoning occurred in 48 patients (38%) including four fatalities. Using the regression analysis, predictive factors of poisoning severity were Glasgow coma score ≤10 (Odds ratio (OR), 11.1; 95% confidence interval (CI), [4.1–33.3], p < 0.0001) and lithium concentration ≥5.2 mmol/l (OR, 6.0; CI, [1.7–25.5], p = 0.005). Ninety-eight patients (77%) developed acute kidney injury according to KDIGO criteria and 22 (17%) were treated with ECTR. Peak lithium concentration ≥5.2 mmol/l (OR, 22.4; CI, [6.4–96.4]; p < 0.0001) and peak creatinine concentration ≥200 μmol/l (OR, 5.0; CI, [1.4–19.2]; p = 0.01) were associated with ECTR use. Only 21/46 patients who presented one of these two criteria were actually treated with ECTR. More significant neurological impairment persisted on discharge in patients not treated with ECTR ( p = 0.0007) despite not significantly shorter length of ICU stay. Conclusions: Lithium poisoning is responsible for severe impairments but rare fatalities. Severity can be predicted on admission using Glasgow coma score and lithium concentration. Our results suggest that ECTR could be indicated if serum lithium ≥5.2 mmol/l or creatinine ≥200 μmol/l.